Self-healing and flexible carbon nanotube/polyurethane composite for efficient electromagnetic interference shielding. (15th July 2020) - Wang, Ting; Yu, Wan-Cheng; Zhou, Chang-Ge; Sun, Wen-Jin; Zhang, Yun-Peng; Jia, Li-Chuan; Gao, Jie-Feng; Dai, Kun; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Electromagnetic interference (EMI) shielding composites are inevitably damaged in the long-term usage which would affect the regular operation of the devices. Hence, the demand for materials with healable and reliable EMI shielding performance has increased. Here, a flexible conductive composite owning both self–healing and EMI shielding functions is facilely developed, with carbon nanotubes (CNTs) as conductive filler and dynamically crosslinked polyurethane bearing Diels–Alder bonds (PUDA) as polymer matrix. The PUDA/CNT composite shows a high EMI shielding effectiveness (EMI SE) of 30.7 dB at 5.0 wt% CNT loading in the range of X-band (8.2–12.4 GHz). And the EMI SE can recover from 16.8 dB for damaged state to 29.8 dB after three times cut/healing cycles, revealing excellent EMI SE retention of 97.1%. The PUDA/CNT composite also exhibits healable tensile properties with an elongation at break up to 571% ± 31% at 2.0 wt% CNT content and self-healing efficiency of 89.2% after the repeatable healing. This work demonstrates a healable EMI shielding composite, which ensures the reliability and long-time use under harsh conditions. Graphical abstract: Image 1 Highlights: The flexible self–healing EMI shielding composite is facilely developed. The composite exhibits excellent mechanical and EMI shielding properties. The composite shows highly efficient self-healing performance based on the Diels-Alder bonds.